Current Trends in Fluid Viscous Dampers with Semi-Active and Adaptive Behavior - Luca Zoccolini; Eleonora Bruschi; Sara Cattaneo; Virginio Quaglini (Applied Sciences, 2023)
Fluid viscous dampers (FVDs) have shown their efficiency as energy-dissipating systems, reducing the effects induced on structures by dynamic loading conditions like earthquakes and winds. In this paper, the evolution of this technology is reviewed, with a focus on the current trends in development from passive to semi-active and adaptive systems and an emphasis on their advances in adaptability and control efficacy. The paper examines the implementation of semi-active FVDs such as electrorheological, magnetorheological, variable stiffness, and variable damping dampers. These devices have a high potential to mitigate the vibrations caused by earthquakes of different intensities. In addition, adaptive FVDs are presented. As semi-active devices, the adaptive ones can adjust their behavior according to the dynamic excitations’ intensity; however, they are able to do that autonomously without the use of any external equipment.